2023
DOI: 10.46234/ccdcw2023.043
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Online Survey on Depression and Anxiety Among the Population Infected or Non-Infected with COVID-19 — China, December 2022

Abstract: What is already known about this topic? The psychological impact of the large-scale infection of the population resulting from the end of lockdown measures in China during the coronavirus disease 2019 (COVID-19) pandemic is unknown. What is added by this report? Among all participants, 55.7% had depression symptoms, with a significant difference between the infected and non-infected groups, and 30.1% had anxiety. Those who were young, unvaccinated, had lower incomes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…The incidence of COVID-19 in EORA patients in this study appeared to be lower than that in the general population or in the same age group in Qin' study ( P < 0.001 and P = 0.013, respectively, χ 2 test), despite previous studies reporting a higher infection risk for RA patients 9,10 . Moreover, the study by Qin et al 2 indicated that elderly individuals exhibited better psychological quality, fewer symptoms of depression and anxiety, better stress-coping abilities and reduced outings during the COVID-19 pandemic compared with young people.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…The incidence of COVID-19 in EORA patients in this study appeared to be lower than that in the general population or in the same age group in Qin' study ( P < 0.001 and P = 0.013, respectively, χ 2 test), despite previous studies reporting a higher infection risk for RA patients 9,10 . Moreover, the study by Qin et al 2 indicated that elderly individuals exhibited better psychological quality, fewer symptoms of depression and anxiety, better stress-coping abilities and reduced outings during the COVID-19 pandemic compared with young people.…”
Section: Discussioncontrasting
confidence: 79%
“…In this study, more than half (58.8%, 60/102) of the EORA patients had COVID-19 from December 2022 through February 2023, and the majority of these patients (93.3%) exhibited Moreover, the study by Qin et al 2 indicated that elderly individuals exhibited better psychological quality, fewer symptoms of depression and anxiety, better stress-coping abilities and reduced outings during the COVID-19 pandemic compared with young people. Fever, cough, expectoration, sore throat, nasal congestion, muscle soreness, fatigue and other symptoms were common in COVID-19 patients with EORA, which was consistent with a study conducted in Zhejiang province from January 17 to February 12, 2020.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations